Payment of Zakat Using Cryptocurrency: A Comparative Study of Indonesia and Malaysia - Adnan Fanani; Anisah Anisah; Nana Srithammasak (Journal Evidence Of Law, 2025)
This study examines the implementation of cryptocurrency-based zakat in Indonesia and Malaysia, with a focus on the differences in legal, Shariah, and technological frameworks. The rise of digital assets presents both opportunities and challenges for Islamic philanthropy, requiring normative clarity and operational innovation. The study employs a qualitative approach, combining normative and comparative methods to analyze fatwas, regulatory documents, and scholarly literature. Findings reveal that Malaysia has developed a mature operational model, integrating state-level fatwas, financial market regulation, and blockchain-based platforms that ensure transparency and accountability in zakat collection. Indonesia, by contrast, remains largely at a conceptual stage, limited by the absence of a comprehensive national fatwa, standardized operational guidelines, and coordinated governance, despite rapid growth in cryptocurrency adoption. The study contributes to the literature by proposing a hybrid governance model that emphasizes the importance of legal certainty, Shariah compliance, and technological adoption for effective implementation. Policy recommendations include integrated regulatory–fatwa frameworks, adaptive nisab and haul calculations, technical mechanisms such as stablecoin conversion, and targeted literacy programs. Cryptocurrency zakat is thus not merely a normative or technical issue but a strategic instrument to advance Islamic financial inclusion, bridge tradition and modernity, and reinforce zakat’s social justice role in the digital economy.